2014
DOI: 10.1016/j.ahj.2014.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between chronic exposure to biomass fuel smoke and markers of right ventricular pressure overload at high altitude

Abstract: Background Chronic exposure to biomass fuel smoke has been implicated in the development of pulmonary hypertension and right ventricular pressure/volume overload through activation of inflammation, increase in vascular resistance and endothelial dysfunction. We sought to compare N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) and echocardiography-derived pulmonary artery systolic pressure (PASP) levels in a high-altitude population-based study in Peru with and without chronic exposure to biomass fuel sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
(44 reference statements)
2
4
1
4
Order By: Relevance
“…Previous studies from our group have examined the relationship of biomass fuel use with RVSP and serum NT-pro-BNP levels in a sample of 153 participants in Puno, 39 and found no relationship, which is consistent with the findings of this study. However, a cross-sectional study in Turkey observed increased pulmonary artery systolic pressure and decreased right ventricular and left ventricular function as measured by myocardial performance indices in self-reported chronic biomass fuel users in comparison with non-users.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies from our group have examined the relationship of biomass fuel use with RVSP and serum NT-pro-BNP levels in a sample of 153 participants in Puno, 39 and found no relationship, which is consistent with the findings of this study. However, a cross-sectional study in Turkey observed increased pulmonary artery systolic pressure and decreased right ventricular and left ventricular function as measured by myocardial performance indices in self-reported chronic biomass fuel users in comparison with non-users.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, we did not find a link between biomass fuel smoke exposure with right heart function or RVSP.While additional echocardiographic studies in association with household air pollution exposure are ongoing, there are very few published studies that examine the changes in cardiac structure and function that are associated with exposure to smoke from biomass fuel use. Previous studies from our group have examined the relationship of biomass fuel use with RVSP and serum NT-pro-BNP levels in a sample of 153 participants in Puno,39 and found no relationship, which is consistent with the findings of this study. However, a cross-sectional study in Turkey observed increased pulmonary artery systolic pressure and decreased right ventricular and left ventricular function as measured by myocardial performance indices in self-reported chronic biomass fuel users in comparison with non-users 40.…”
supporting
confidence: 91%
“…Additionally, a cross sectional study of 266 individuals in Puno, Peru found that chronic exposure to biomass fuel smoke was associated with increased carotid intima-media thickness and a higher prevalence of carotid atherosclerotic plaques 106 . However, contrary to what was previously hypothesized, in a sample from the same Peruvian cohort there was no association between biomass fuel use with elevated NT pro-BNP or right ventricular systolic pressure by echocardiography 107 . A small echocardiography study in a single hospital in Turkey observed that biomass fuel users had increased right ventricular systolic pressure and decreased left and right ventricular myocardial indices, indicating decreased biventricular systolic function 108 .…”
Section: Household Air Pollution From Biomass Fuel Usecontrasting
confidence: 99%
“…supplementary material is available online at www.liebertpub .com/ham). Two operators, blinded to participant characteristics, performed a limited echocardiogram with a portable ultrasound system (MicroMaxx, Sonosite, Bothell, WA) as described previously (Caravedo et al, 2014). PASP was estimated using the simplified Bernoulli equation: PASP = 4v 2 + RAP, where v is the peak tricuspid regurgitation jet velocity (meters per second) and RAP is the estimated right atrial pressure as per the American Heart Association Consensus guidelines (McQuillan et al, 2001;Lam et al, 2009;Rudski et al, 2010;Caravedo et al, 2013).…”
Section: Echocardiographymentioning
confidence: 99%